Lipoxygenase inhibiting activity of some Malaysian plants - Chung, L.Y.; Soo, W.K.; Chan, K.Y.; Mustafa, Mohd Rais; Goh, S.H.; Imiyabir, Z. (Taylor & Francis, 2009)
In this study 160 plant samples representing more than 30 plant families collected from the Malaysian forests were assessed for their ability to inhibit lipoxygenase activity. The lipoxygenase inhibiting activity was measured using the 96-well microplate-based ferric oxidation of xylenol orange (FOX) assay. The screening parameters, including z’ factor, indicated that the assay method adopted was robust and suitable for highthroughput screening. In the preliminary screen, four plant extracts displayed inhibitory activity of 70% or higher. The active plant extracts were isolated from Agelaea borneensis Merr. (Connaraceae) (bark) (IC 50,1.6 μg/mL), Chisocheton polyandrus Merr. (Meliaceae (bark) (3 μg/mL), Garcinia cuspidata King (Guttiferae) (bark) (28.3 μg/mL) and Timonius flavescens Baker (Rubiaceae) (leaf) (8.9 μg/mL).